Skull Ecomorphology of Megaherbivorous Dinosaurs from the Dinosaur Park Formation (Upper Campanian) of Alberta, Canada - Mallon, Jordan C.; Anderson, Jason S. (PLOS ONE, 2013)
Megaherbivorous dinosaur coexistence on the Late Cretaceous island continent of Laramidia has long puzzled researchers, owing to the mystery of how so many large herbivores (6–8 sympatric species, in many instances) could coexist on such a small (4–7 million km2) landmass. Various explanations have been put forth, one of which–dietary niche partitioning–forms the focus of this study. Here, we apply traditional morphometric methods to the skulls of megaherbivorous dinosaurs from the Dinosaur Park Formation (upper Campanian) of Alberta to infer the ecomorphology of these animals and to test the niche partitioning hypothesis. We find evidence for niche partitioning not only among contemporaneous ankylosaurs, ceratopsids, and hadrosaurids, but also within these clades at the family and subfamily levels. Consubfamilial ceratopsids and hadrosaurids differ insignificantly in their inferred ecomorphologies, which may explain why they rarely overlap stratigraphically: interspecific competition prevented their coexistence.